Experience of 10 years of application of OTSC-Assisted Full-Thickness Interventions in the Gastrointestinal Tract: Endoscopic Full-Thickness Resection (eFTR) and Fistula Closure (Perioperaciina Medicina, 2026)
Background: Closure of full-thickness defects of the gastric and esophageal wall remains a major challenge in contemporary endoscopy, particularly following endoscopic full-thickness resection (eFTR) and in the management of fistulas. The over-the-scope clip (OTSC) system has emerged as a promising tool for defect closure.Objective: To evaluate the efficacy and safety of the OTSC system in the closure of both intentionally created and spontaneous full-thickness defects of the gastrointestinal wall.Materials and Methods: A retrospective analysis of four cases of OTSC-Assisted Full-Thickness Interventions in the Gastrointestinal Tract treated between 2015 and 2025 was performed. Two patients underwent eFTR (for early gastric cancer and aberrant pancreatic tissue in the stomach), while two patients underwent endoscopic closure of chronic fistulas (tracheoesophageal fistula and surgical gastrostomy).Results: Technical success was achieved in all cases (100 %; 95 % СІ 40–100 %). Clinical success, defined as R0 resection in eFTR and complete fistula closure, was observed in 75 %; 95 % СІ 22–98 % (3/4 cases). One patient experienced fistula recurrence at 3 months, which was successfully managed with repeat OTSC application.Conclusions: The OTSC system provides an effective and safe method for managing full-thickness gastrointestinal wall defects, regardless of etiology (iatrogenic after eFTR or chronic fistulas).
Keywords: OTSC system; endoscopic full-thickness resection (eFTR); gastrointestinal wall defect; fistula closure; endoscopic therapy